The Effect of Quick Ratio (QR), Debt to Equity Ratio (DER), Net Profit Margin (NPM), and Price to Book Value (PBV) On Stock Prices of Food and Beverage Companies in the Period 2011-2020 - Kumba Digdowiseiso; Nurul Fadillah (Budapest International Research and Critics University, 2022)
The purpose of this study was to examine and analyze The Influence of Quick Ratio (QR), Debt to Equity Ratio (DER), Net Profit Margin (NPM), and Price to Book Value (PBV) on Stock Prices of Food and Beverage Sector Companies in Indonesia. Indonesia Stock Exchange Period 2011-2020. The data used in this study is secondary data obtained from the official website of the Indonesia Stock Exchange, Yahoo Finance and through the websites of each company. The research sample selected was 10 companies in the food and beverage sector listed on the Indonesia Stock Exchange in the period 2011-2020. Secondary data can be analyzed using panel data linear regression model. Purposive Sampling is a sampling technique used in this study according to several required criteria. The data analysis used was panel data regression analysis using the STATA 16 program.